Evaluation of Knowledge, Attitude and Behavior of Workers towards Occupational Health and Safety - H Sanaei Nasab; R Tavakoli; F Ghofranipour; A Kazemnejad; A Khavanin (Tehran University of Medical Sciences, 2009)
Background: Studies show that about 90% of accidents occur because of unsafe behavior and human errors. Even if workers do not have the right knowledge, attitude and behavior toward safety measures in a safe workplace, all efforts for an accident-free workplace will be in vain. This study aims to determine the level of knowledge, attitude and behavior of workers toward occupational health and safety. Methods: This descriptive cross-sectional study was carried out on workers in Mahshahr Razy Petrochemical Complexm Ahwaz, Iran. A sample size of 210 was randomly selected. Data collection tool was a researcher-made questionnaire. Questionnaire's validity was gained by content-validity and its reliability was validated by Kronbach's alpha. Data was analyzed using SPSS 13. Results: Mean age of workers was 31.1 years. The mean of their knowledge, attitude and behavior was reported 26.02, 153.18 and 36, respectively. 52.9% of workers had low, 36.7% moderate and 10.5% high level of knowledge. In addition, 75.7% of the subjects had a positive attitude towards occupational health and safety; 30% of workers had low safety behavior and 70% had safe behavior. The mean of knowledge grade shows a significant relationship with education level. A same relationship was reported for the mean of attitudes and behavior with age. Conclusion: Managers should design and implement educational interventions to promote knowledge, attitude and safe behaviors of workers.